THE SPATIAL AND SECTORAL CONCENTRATION OF THE FOREIGN DIRECT INVESTMENTS IN ROMANIA - Marius Voicilas, Dan (Economics of Agriculture, 2007)
A territorial analysis of the foreign direct investments (FDI) in Romania shows major differences at all levels and in many fields. Among the eight Romanian economic development regions, there are a few which have closer indicators with the level of other countries in European Union (EU), but still many other far from the requirements of a member state of EU. A sectoral analysis of the FDI in Romania demonstrates a big imbalance between branches. Some of them were more attractive compared with the others. The investments generally and the investments in rural area and agri-food sector especially, acquire a special importance, as they are closely linked to the natural environment and the population. In the context of the transformations in the last years, the agriculture needs major investments in order to recover the lost capital due to the lack of stability and clear policy in the first years of transition. The lack of domestic capital claims for international funds and foreign investments. These are only a part of the arguments supporting the idea that, the foreign capital in Romania is welcome and necessary for the recovery of some sectors of activity, for improvement of the state of regions and for evening out of the disparities between them. The analysis of the Romanian sectors and regions, together with the investment policy and foreign capital flows evolution in economy will strengthen the above-mentioned arguments and reveal the present drawbacks and the need to accelerate the investment process.